2016
DOI: 10.1111/jpi.12342
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin improved potassium content in Malus under different stress conditions

Abstract: Melatonin mediates many physiological processes in plants. We investigated its role in regulating growth, potassium uptake, and root system architecture under three types of stress: salinity or a deficiency of all nutrients in Malus hupehensis Rehd., as well as a K deficiency in Malus rockii Rehd. Each treatment caused a reduction in growth rates and disrupted the absorption of potassium. However, pretreatment with 0.1 mmol/L melatonin significantly alleviated such inhibitions. The addition of melatonin also u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 62 publications
5
57
0
Order By: Relevance
“…It is well known that various stressors induce melatonin production in plants as well as in animals (Byeon et al, 2012; Li C. et al, 2016; Xu et al, 2016). This is considered as self-defense of organisms against external insults (Tan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that various stressors induce melatonin production in plants as well as in animals (Byeon et al, 2012; Li C. et al, 2016; Xu et al, 2016). This is considered as self-defense of organisms against external insults (Tan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin was identified in plants in Dubbels et al (1995) and Hattori et al (1995). Since then it has been reported to exist in many plants and plant products (Ramakrishna et al, 2012; Yip et al, 2013; Shi et al, 2015b; Zhao et al, 2015a; Li C. et al, 2016; Ma et al, 2016; Xu et al, 2016). Different from other antioxidants, it is an amphiphilic molecule which makes it distribute in all cellular compartments including cytosol, membrane, mitochondria and chloroplasts (López et al, 2009; Byeon et al, 2013; Back et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Large numbers of experiments involving exogenous application of melatonin to a series of plant species indicated that melatonin acts as a biostimulator in plants 6 by enhancing a myriad of defense responses against abiotic stresses, including oxidative stress, 7-10 high temperature, 10,11 cold, [12][13][14] senescence, 15,16 drought, 17,18 and salt, 19,20 as well as biotic stress such as pathogen attacks. [21][22][23][24][25][26][27][28][29] In addition to the defense responses, melatonin has also been implicated in promoting plant growth processes, such as seedling growth, 30,31 flowering, 32 nutrient absorption, 33 and fruit ripening, 34 suggesting a potential role of melatonin as a plant growth factor. 6 Recently, the relationship between melatonin and cadmium has been a focus of attention because melatonin treatment not only attenuated the toxic effects of cadmium stress in tomato and rice, but melatonin levels were shown to be upregulated in response to cadmium to such an extent that this heavy metal is the most effective elicitor of melatonin biosynthesis in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin itself is an effective antioxidant, which directly scavenges ROS and whose metabolite, N1 -acetyl- N2 -formyl-5-methoxykynuramine (AMFK), can also directly and efficiently scavenge ROS (Tan et al, 2007a; Manchester et al, 2015). Beyond this, melatonin also possesses antioxidant activity operating by stimulating antioxidant enzymes and augmenting antioxidants and involving the ascorbate–glutathione (AsA–GSH) cycle to scavenge excess ROS (Wang et al, 2012; Li et al, 2015; Chao et al, 2016). However, previous studies on the effects of melatonin on the AsA–GSH cycle under stress conditions are based mainly on whole leaves.…”
Section: Introductionmentioning
confidence: 99%